1992
DOI: 10.1007/bf03159983
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-induced acute cholinergic neurotoxicity in rat

Abstract: In the present study the acute effect of intravenous aluminum chloride (1 mg/kg) on choline acetyltransferase (ChAT) and acetylcholinesterase (AChE) activities of rats was investigated. Aluminum was found to cross the blood-brain barrier (BBB) as indicated by the detection of aluminum in the cerebrospinal fluid (CSF) 30 min after femoral vein injection. Two hours following aluminum injection, ChAT activity in the basal forebrain and hippocampus was significantly reduced by 30% and 22%, respectively, whereas no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…We suppose that the greatest changes in the plasma Al concentrations have already occurred before the first sampling of plasma. The observed elevation of plasma aluminum concentration in our experiment could be sufficient for the movement of Al into the brain, since aluminum was found to cross the blood-brain barrier, and it was detected in the cerebrospinal fluid 30 minutes after intravenous application of aluminum chloride (1 mg/kg) to rats femoral vein (28). Examination of storage and distribution of aluminum in various tissues in rats, after application of aluminum through gastric tube, revealed that the maximal concentration of aluminum in liver was detected after 0.5 hours, in kidney after 1 hour and in the brain 48 hours after aluminum intake (29).…”
Section: Discussionsupporting
confidence: 49%
“…We suppose that the greatest changes in the plasma Al concentrations have already occurred before the first sampling of plasma. The observed elevation of plasma aluminum concentration in our experiment could be sufficient for the movement of Al into the brain, since aluminum was found to cross the blood-brain barrier, and it was detected in the cerebrospinal fluid 30 minutes after intravenous application of aluminum chloride (1 mg/kg) to rats femoral vein (28). Examination of storage and distribution of aluminum in various tissues in rats, after application of aluminum through gastric tube, revealed that the maximal concentration of aluminum in liver was detected after 0.5 hours, in kidney after 1 hour and in the brain 48 hours after aluminum intake (29).…”
Section: Discussionsupporting
confidence: 49%
“…Choline is then covalently linked with an activated acetyl unit from acetylCoA to form acetylcholine by choline O-acetyltransferase. In spite of some authors reporting no effects of aluminium on this enzyme activity [114][115][116][117], a decline of choline Oacetyltransferase activity following in vivo exposure to aluminium has been consistently observed [93,[118][119][120][121][122][123][124][125][126][127], which can be, in part, warranted by cyclooxygenase-2 induced reduction of choline O-acetyltransferase protein expression [128]. In fact, gene up-and down-regulation of cyclooxygenase-2 and choline O-acetyltransferase, respectively, have been detected in aluminium-treated cells in culture [79].…”
Section: Neurotransmitter Synthesis and Storagementioning
confidence: 88%
“…The effect of aluminium on acetylcholinesterase has been studied either in vivo or in vitro (i.e. [114,116,120,123,125,145,158,[206][207][208][209][210][211][212][213][214][215][216][217][218][219][220][221][222][223]), and both, stimulatory and inhibitory, effects have been reported.…”
Section: Inactivation Of Neurotransmittersmentioning
confidence: 99%
“…Studies have established AChE as a biomarker for several environmental contaminants (Naravaneni and Jamil 2007;Senger et al 2006), and it has been suggested that aluminum interacts with the cholinergic system in both in vitro and in vivo systems. However, the results of these investigations are conflicting because some authors report decreases in AChE activity (Hetnarski et al 1980;Kumar 1998) whereas others report an activation of AChE in the presence of aluminum (Peng et al 1992;Sarkarati et al 1999;Zatta et al 1994Zatta et al , 2002.…”
Section: Introductionmentioning
confidence: 93%